Acetylcholine regulation of GnRH neuronal activity: A circuit in the medial septum - Shostak, David M.; Constantin, Stephanie; Flannery, Jill; Wray, Susan (Frontiers in Endocrinology, 2023)
In vertebrates, gonadotropin-releasing hormone (GnRH)-secreting neurons control fertility by regulating gonadotrophs in the anterior pituitary. While it is known that acetylcholine (ACh) influences GnRH secretion, whether the effect is direct or indirect, and the specific ACh receptor (AChR) subtype(s) involved remain unclear. Here, we determined 1) whether ACh can modulate GnRH cellular activity and 2) a source of ACh afferents contacting GnRH neurons. Calcium imaging was used to assay GnRH neuronal activity. With GABAergic and glutamatergic transmission blocked, subtype-specific AChR agonists and antagonists were applied to identify direct regulation of GnRH neurons. ACh and nicotine caused a rise in calcium that declined gradually back to baseline after 5-6 min. This response was mimicked by an alpha3-specific agonist. In contrast, muscarine inhibited GnRH calcium oscillations, and blocking M2 and M4 together prevented this inhibition. Labeling for choline acetyltransferase (ChAT) and GnRH revealed ChAT fibers contacting GnRH neurons, primarily in the medial septum (MS), and in greater number in females than males. ChAT positive cells in the MS are known to express p75NGFRs. Labeling for p75NGFR, ChAT and GnRH indicated that ChAT fibers contacting GnRH cells originate from cholinergic cells within these same rostral areas. Together, these results indicate that cholinergic cells in septal areas can directly regulate GnRH neurons.